DETERMINANTS OF HYPERTENSION IN KRUENG BARONA JAYA HEALTH CENTER, ACEH BESAR DISTRICT - Wati, Sukma; Zahara, Hafni; Putri, Rosalia (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2023)
This research was conducted to investigate the factors influencing the development of hypertension among patients at the Krueng Barona Jaya Health Center in Aceh Besar District. Employing a quantitative cross-sectional research design, the study analyzed data from a sample of 87 individuals selected from a total population of 641. The study focused on several potential determinants of hypertension, including gender, age, family history, physical activity levels, dietary habits, and smoking status. Statistical analysis using the chi-square test revealed significant associations between hypertension and three factors: gender, age, and diet. These findings suggest that being female, older, and having specific dietary patterns increased the likelihood of developing hypertension in this population. Conversely, family history and physical activity levels were not found to be significantly associated with hypertension in this particular study. These results highlight the importance of considering gender, age, and dietary modifications in hypertension prevention and management strategies for the population served by the Krueng Barona Jaya Health Center.